Fluorescence molecular imaging technology: a promising new strategy for the diagnosis and treatment of gynecologic tumors - Li, Kailang; Huang, Bifan; Jiang, Jin (Frontiers in Bioengineering and Biotechnology, 2026)
Gynecologic malignancies such as ovarian, endometrial, and cervical cancers are characterized by challenges in early diagnosis and high therapeutic complexity, creating an urgent need for more precise imaging techniques. Fluorescence molecular imaging, a modality with high sensitivity and high spatial resolution, has demonstrated considerable value in tumor diagnosis and therapy in recent years. Its application in gynecologic oncology is rapidly expanding. By using tumor-specific molecular probes to label neoplastic tissues, this technology enables real-time intraoperative navigation and visualization of tumor lesions and their local features, thereby significantly improving surgical accuracy and therapeutic outcomes. This review summarizes the basic principles of fluorescence imaging, recent advances in molecular probe design, and developments in imaging devices. It places particular emphasis on the value of fluorescence molecular imaging in the diagnosis and precision treatment of gynecologic tumors, aiming to provide systematic theoretical guidance and technical support for related research and clinical practice.